The Social Impact of VR Technology on Society: A Systematic Literature Review - Bakti Amirul Jabar; Millia Azmi; Graciel Hernando; Jurike V Moniaga; Angelique Aurielle Alpaullivarez (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
Humans are social creatures who usually interact directly. But as technology develops, interactions also use the technology. One of the many popular technologies in the 4.0 era is VR technology. An example of this technology is the metaverse, a combination of the real and virtual worlds. This paper presents a research review to analyze the social impact of Virtual Reality: technology with metaverse. This paper uses a systematic literature review (SLR) as the method. The research was conducted based on the RQ that had been made. There are 18 related articles generated from the search, then reviewed. This study concludes that Social VR has three impacts: Social Presence Illusion, Virtual Embodiment, and the Proteus Effect. In addition, we also explain the ways to create a safe social VR environment, such as by playing with family and friends, educating the public about VR technology, and suggesting that the platform provides an age limit for playing in a VR environment.